Computer designed solar concentrator - Omar, Aliman; Ismail, Daut; Muzamir, Isa; Mohd Rafi, Adzman (International Association of Science and Technology for Development (IASTED)/ACTA Press, 2009)
Link to publisher's homepage at http://www.iasted.org/